If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = x + 6 + -2x Reorder the terms: x = 6 + x + -2x Combine like terms: x + -2x = -1x x = 6 + -1x Solving x = 6 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. x + x = 6 + -1x + x Combine like terms: x + x = 2x 2x = 6 + -1x + x Combine like terms: -1x + x = 0 2x = 6 + 0 2x = 6 Divide each side by '2'. x = 3 Simplifying x = 3
| 4x=5-2x+3-8+7x-4x*3-6 | | 3x(3)+1=10 | | 2x^2=51.85 | | m/17=9 | | 3y=3-x | | (3x+10)(3x+10)= | | x/-5-1=1 | | (12x^2(x^-3)^-4)/6x^5 | | 15x*4+18x=156 | | 2x+46+14-4x=16x+2x | | 8#/9=16 | | 8x-57=2x+3 | | dy/dx=cot^2x | | 4(5c+3)=9c+7 | | 30+(5y-8)+(11x-9)=180 | | 5x-3+4x*9-5x*3-4+2x-5+2=8 | | -11u-8+3u=247 | | dy/dx=cot^2 | | 18x=156 | | C/6-8=2 | | 2(4x-2)-5x=18 | | y=cot^2dx | | 4x*2*2-4x+3-5=5+0 | | 60x^2-59x-20=0 | | 4s+f=156 | | 5m-10=8m+14 | | -9v=-108 | | 5+4y+3y+2=1-2 | | (24m^-2n^4)^-2/(16m^3n^-5)^-2 | | 5+8+2+4x-8x+2+7+3=x | | 3x-4=1/4(12-16x) | | 5x-2+4+3x*6=28x-2-2 |